Fragments of Altar Retables of Late Mediaeval Date in Scotland - Richardson, James S (Proceedings of the Society of Antiquaries of Scotland, 1928)
A retable of late mediaeval date consisted of a number of tables or panels carved in relief, set in a framework of architectural character, and sometimes furnished with hinged shutters. This screen occupied a position immediately above the back of the altar. The scenes carved on the tables were in sets, the most usual being those depicting the "Passion," and the "Life of the Virgin"; other sets illustrated the Bible life of St John the Baptist, the Martyrdom of St Catharine, and episodes in the lives of saints and martyrs. Owing to the destruction of the actual retables and of documentary evidence it is unknown to what extent this type of altar sculpture was in use in Scotland. Many of the Scottish mediaeval churches have unbroken wall-spaces at the back of the altar sites, designed for the display of reredoses or retables. Fragments considered come from Rosslyn Chapel, Paisley Abbey, Mains Kirkyard, near Dundee, St Michael's, Linlithgow and St Salvator's College Kirk, St Andrew's.